The Interplay Between Cervicovaginal Microbial Dysbiosis and Cervicovaginal Immunity - Wang, Ya; Wang, Xiaoli; Zhu, Meiling; Ge, Li; Liu, Xiaochen; Su, Kaikai; Chen, Zhengzheng; Zhao, Weidong (Frontiers in Immunology, 2022)
The cervicovaginal microbiota plays a key role in the health and reproductive outcomes of women. In reality epidemiological studies have demonstrated that there is an association between the structure of cervicovaginal microbiota and reproductive health, although key mechanistic questions regarding these effects remain unanswered and understanding the interplay between the immune system and the structure of the cervicovaginal microbiota. Here, we review existing literature relating to the potential mechanisms underlying the interaction between vaginal microbes and the immune system; we also describe the composition and function of the microbiome and explain the mechanisms underlying the interactions between these microbial communities and various aspects of the immune system. Finally, we also discuss the diseases that are caused by disorders of the reproductive tract and how the immune system is involved. Finally, based on the data presented in this review, the future perspectives in research directions and therapeutic opportunities are explored.